Association between body roundness index and reproductive outcomes in patients with polycystic ovary syndrome: a secondary analysis based on PCOSAct - Yu, Jiannan; Ge, Hang; Gao, Zhuwei; Feng, Jiaxing; Gao, Yue; Cong, Jing; Zhu, Mengyi; Shi, Baichao; Guan, Muxin; Gao, Jingshu; Wu, Xiaoke (Frontiers in Nutrition, 2026)
BackgroundObesity, especially visceral obesity, is highly prevalent in women with polycystic ovary syndrome (PCOS) and may adversely affect fertility outcomes. Body roundness index (BRI) is an anthropometric indicator of visceral adiposity, yet evidence linking BRI to key reproductive outcomes remains limited in PCOS.MethodsThis secondary analysis included 998 Chinese women from the Polycystic Ovary Syndrome Acupuncture and Clomiphene Trial (PCOSAct). Baseline BRI was calculated from waist circumference and height measurements, and reproductive outcomes were obtained after interventions. Baseline BRI was calculated from height, weight, and waist circumference and analyzed as quartiles (Q1: < 2.97, Q2: 2.97–3.78, Q3: 3.78–4.87, Q4: ≥ 4.87) and as a continuous variable. Logistic regression models estimated odds ratios (ORs) and 95% confidence intervals (CIs) for ovulation, conception, clinical pregnancy, and live birth, adjusting for interventions, age, systolic and diastolic blood pressure (SBP and DBP). Nonlinearity was assessed using restricted cubic splines (RCS), with model fit compared against linear models using likelihood ratio tests.ResultsIn total, 780 participants regained ovulation, 320 achieved conception, 218 attained clinical pregnancy, and 205 had a live birth. Higher BRI quartiles were associated with worse anthropometric, metabolic, and hormonal profiles at baseline. In regression analyses, higher BRI quartiles were generally associated with lower odds of reproductive outcomes, with significant trends across quartiles after adjustment. Restricted cubic spline analyses showed no evidence of nonlinearity for ovulation or conception (P-nonlinear = 0.951 and 0.301), but significant nonlinearity for clinical pregnancy and live birth (P-nonlinear = 0.016 and 0.025).ConclusionHigher BRI was associated with poorer reproductive outcomes in women with PCOS, with evidence of nonlinear associations for clinical pregnancy and live birth. BRI may provide clinically relevant information beyond general adiposity for reproductive risk stratification in PCOS.